Persistent inter-industry wage differences: Rent sharing and opportunity costs - John M. Abowd; Francis Kramarz; Paul Lengermann Lengermann; Kevin L. McKinney; Sébastien Roux (IZA Journal of Labor Economics, 2012)
We reconsider the potential for explaining inter-industry wage differences by decomposing those differences into parts due to individual and employer heterogeneity, respectively. Using longitudinally linked employer-employee data, we estimate the model for the United States and France. The part arising from individual heterogeneity can be theoretically and empirically related to the worker's opportunity wage rate. The part arising from employer heterogeneity can similarly be related to product market quasi-rents and relative bargaining power. We find that these two variables are highly correlated with both parts of the differential in France. Although the U.S. inter-industry wage differentials are strongly correlated with those in France, the decomposition is more nuanced in the American data, where the opportunity wage rate and the product market conditions are related to both the personal and employer heterogeneity.
Keywords: J31; J50; L10; 330; Inter-industry wage differentials; Matched employer-employee data; Quasi-rents; Sektorale Lohnstruktur; USA; Frankreich